Evaluation of a rainbow trout - Sanchez, Ivan O; Sanguino, Wilmer O; Gomez, Ariel C; Garcia, Roberto C (Revista MVZ (Medicina Veterinaria y Zootecnia), 2014)
Objective. To evaluate a water recirculation system for rainbow trout fish cultures at the recirculating laboratory of the Aquaculture Engineering Production Program of University of Narino. Materials and Methods. 324 rainbow trout (Oncorhynchus mikyss) fries were cultured in 12 plastic tanks with a capacity of 250 L in an aquaculture recirculating system the treatment system of which was made up by a conventional sedimentation tank, a fixed stand upflow biofilter with recycled PVC tube pieces and a natural degassing system; the sedimentation unit effluent was pumped up to a reservoir tank using a 2 HP centrifugal pump after being subject to gravity through the biofilter and to be then distributed to the 12 culture units to which a constant amount of air from a blower was injected. Results. The water treatment system removed 31% of total suspended solids, 9.5% of total ammonia nitrogen, and increased dissolved oxygen to the final effluent in 6.5%. An increase of 305% in biomass was calculated during 75 days, the mortality percentage registered throughout the study period was 4.9%. Conclusions. The water treatment system maintained the physicochemical water quality parameters within the values recommended for the species. The increase in weight and size, food conversion, mortality and biomass production reported normal values for rainbow trout fish culture in recirculating systems. Key words: Aquaculture, cultivation, treatment, trout, water recirculation (Source: CAB, DeCS). Objetivo. Evaluar un sistema de recirculacion de agua para cultivo de trucha arcoiris en el laboratorio de recirculacion del Programa Ingenieria en Produccion Acuicola de la Universidad de Narino. Materiales y metodos. Se cultivaron 324 alevinos de trucha arco iris (Oncorhynchus mikyss) en 12 tanques plasticos de 250 L de capacidad en un sistema de recirculacion para acuacultura cuyo sistema de tratamiento estuvo constituido por un sedimentador convencional, un biofiltro de flujo ascendente con medio soporte fijo conformado por segmentos reciclados de tubos PVC, y un sistema de desgasificacion natural; el efluente del sedimentador fue elevado a un tanque reservorio por medio de una bomba centrifuga de 2 HP para despues pasar por gravedad a traves del biofiltro y posteriormente ser distribuido a las 12 unidades de cultivo a las que de manera permanente se inyecto aire proveniente de un blower. Resultados. El sistema de tratamiento del agua removio 31% de los solidos suspendidos totales; 9.5% del nitrogeno amoniacal total, e incremento el oxigeno disuelto al efluente final en un 6.5%. Se calculo un incremento de la biomasa del 345% en los 75 dias, el porcentaje de mortalidad registrado durante todo el periodo de estudio fue del 4.9%. Conclusiones. El sistema de tratamiento mantuvo los parametros fisico-quimicos de la calidad de agua dentro de los rangos requeridos por la especie. El incremento de peso y talla, la conversion alimenticia, la mortalidad y la produccion de biomasa reportaron valores normales para produccion de trucha en sistemas de recirculacion. Palabras clave: Acuicultura, cultivo, recirculacion del agua, tratamiento, trucha (Fuente: CAB, DeCS).